2018
DOI: 10.1002/cctc.201801531
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Oxidative Palladium‐Catalyzed Regioselective Synthesis of 3‐Arylindoles from N−Ts‐Anilines and Styrenes: A Computational Study

Abstract: Palladium (Pd)‐catalyzed intermolecular oxidative annulation represents as an attractive approach to regioselective synthesis of 2/3‐arylindoles, but the unexpected regioselectivity remains to be one of the most challenging questions in this field. Herein, we present a systematically theoretical study on the Pd‐catalyzed regioselective synthesis of 3‐arylindoles from N−Ts‐anilines and styrenes with the presence of oxidant, special ligand, and benzoquinone (BQ) additive. A refined mechanism, in which the single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 57 publications
1
8
0
Order By: Relevance
“…Researchers are more concerned about Pt due to its excellent catalytic performance, but Pt is too expensive to industrial production. Pd and Pt are in the same group, have similar chemical properties, are more economical, and can be used for the activation of C−H bonds . In this study Pd was chosen as catalyst to explore the different reaction pathway of ethane/CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Researchers are more concerned about Pt due to its excellent catalytic performance, but Pt is too expensive to industrial production. Pd and Pt are in the same group, have similar chemical properties, are more economical, and can be used for the activation of C−H bonds . In this study Pd was chosen as catalyst to explore the different reaction pathway of ethane/CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…However, experimental results show that the activation takes place on the carbon A ortho to the nitrogen. A recent computational study on a similar palladium catalyst suggested that the activation does indeed proceed through the nitrogen coordination to palladium (Qiao et al., 2019). The following acetate-mediated N−H deprotonation leads to a four-member transition state that directs the reaction to position A.…”
Section: Resultsmentioning
confidence: 99%
“…(3) Which step is the stereoselectivity‐determining step of chiral phosphine‐catalyzed [4 + 2] reaction? In order to solve the above mentioned problems, we intend to carry out a theoretical study on this kind of reaction by using the DFT method, which has been proved to be an effective and powerful tool for the mechanistic study of organocatalytic, [ 36–43 ] transition‐metal catalyzed [ 44–46 ] reactions.…”
Section: Introductionmentioning
confidence: 99%